Repeat antimicrobial susceptibility testing of identical isolates. - Thomson, R B (1989)
Duplicate antimicrobial susceptibility test results were reviewed over a 1-year period to determine whether repeat testing of sequential isolates with the same identification from the same patient and specimen site was necessary. In our institution, repeat testing is always needed for coagulase-negative staphylococci and Pseudomonas aeruginosa and is needed after 3 days for members of the family Enterobacteriaceae, but it is not routinely necessary for Staphylococcus aureus.